Coalition Politics and Federalism (Springer International Publishing, 2018)
This book analyzes the verticalization of coalition cabinets from the national to the sub-national level. Presenting case studies for countries with federal systems of government, such as Argentina, Australia, Brazil, Canada, Germany, and India, as well as those focusing on states with hybrid systems of government, such as Italy, the contributors analyze multilevel government formation processes to identify vertical congruence between national and sub-national coalitions. The book also examines various factors affecting the degree of congruence of political coalitions, such as the degree of decentralization, federalization and institutionalization of political systems, as well as cleavage structure. This book will be a valuable resource for all scholars interested in coalition politics, as well as for politicians and practitioners in government and parliament.